2020
DOI: 10.13040/ijpsr.0975-8232.11(9).4321-28
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This experimental study had approved by animal ethics of Central Drug Research Institute, Lucknow, and had undertaken to evaluate the antidyslipidemic and anti-oxidant activities of Nigella Sativa (N. Sativa), Hindi name Kalonji seeds extract in two models of hyperlipidemia. 1-triton and 2cholesterol-rich high-fat diet (HFD) induced hyperlipidemia. N. Sativa and Gemfibrogil were macerated with 2% aqueous gum acacia, and the suspension had fed orally to rats at a dose of 500 mg/Kg (b.w.p.o.) respectively. Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Numerous studies proposed N. sativa as an adjuvant therapy in diabetes control, since it revealed a significant reduction in glucose values following oral glucose tolerance test (OGTT), fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) levels, and insulin resistance, and also an escalation in serum fasting insulin concentrations ( 18 20 ), while recent research reported that N. sativa supplementation increased the levels of glycemic control components ( 21 ). Furthermore, it has been demonstrated that N. Sativa extract could increase the high-density lipoprotein cholesterol (HDL-C) concentration through rising the activity of plasma lecithin cholesterol acetyltransferase (LCAT), and it could also exert its antioxidant effects by enhancing the activities of antioxidant enzymes, including catalase and glutathione peroxidase, leading to its potential efficacy in amelioration of atherosclerosis ( 22 , 23 ). However, there are still strong pieces of evidence suggesting null effects of N. sativa on biomarkers of inflammation ( 21 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies proposed N. sativa as an adjuvant therapy in diabetes control, since it revealed a significant reduction in glucose values following oral glucose tolerance test (OGTT), fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) levels, and insulin resistance, and also an escalation in serum fasting insulin concentrations ( 18 20 ), while recent research reported that N. sativa supplementation increased the levels of glycemic control components ( 21 ). Furthermore, it has been demonstrated that N. Sativa extract could increase the high-density lipoprotein cholesterol (HDL-C) concentration through rising the activity of plasma lecithin cholesterol acetyltransferase (LCAT), and it could also exert its antioxidant effects by enhancing the activities of antioxidant enzymes, including catalase and glutathione peroxidase, leading to its potential efficacy in amelioration of atherosclerosis ( 22 , 23 ). However, there are still strong pieces of evidence suggesting null effects of N. sativa on biomarkers of inflammation ( 21 , 24 ).…”
Section: Introductionmentioning
confidence: 99%